«ПРОИЗВОДСТВО ПРИСУТСТВИЯ» И АРХЕОЛОГИЯ: ТОЧКИ СОПРИКОСНОВЕНИЯ - САВЕЛЬЕВА, А. К. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 1970)
В статье анализируются точки соприкосновения в культуре археологии и программыгуманитарных исследований Ханса Ульриха Гумбрехта. Современная археологиянасчитывает несколько направлений, наиболее важными из них являются когнитивнаяархеология и пост-процессуализм (археологическая версия постмодернизма). Вгуманитарных науках археология представляется альтернативой текстуальным подходам,такой концептуальной традицией, которая досконально исследует материальные факторыкоммуникации и воплощает в себе «присутствие». Междисциплинарные методы иинтерпретационное богатство современной археологической науки фактически делают ееметодологической базой для исследования «культур присутствия».Ключевые слова: присутствие, материальные факторы коммуникации, археология,герменевтика, семиотика, знак, значениеSavelieva A.K. «PRODUCTION OF PRESENCE» AND ARCHAEOLOGY: POINTS OFCONTIGUITY The article analyses points of contiguity of archaeology and Hans Ulrich Gumbrechtprogram of humanitaran research in the culture. Contemporary archaeology has several branches,the most important of them are cognitive archaeology and post-prosessualism (the archaeologicalversion of postmodernism). In the Humanitarian sciences archeology appears to be an alternativeto textual approaches, such conceptual tradition which studies thoroughly the material factors ofcommunication and embodies the «Presence». Interdisciplinary methods and interpretative richnessof modern archaeological science actually make it the methodological basis of research «thecultures of Presence».Keywords: Presence, material factors of communication, archaeology, hermeneutics, semiotics,sign, meaningСавєльєва О.К. «ВИРОБНИЦТВО ПРИСУТНОСТІ» ТА АРХЕОЛОГІЯ: ТОЧКИЗІТКНЕННЯ У статті аналізуються точки зіткнення в культурі археології і програмигуманітарних досліджень Ганса Ульриха Гумбрехта. Сучасна археологія налічує декільканапрямів, найбільш важливими з яких є когнітивна археологія і пост-процесуалізм(археологічна версія постмодернізму). У гуманітарних науках археологія постаєальтернативою текстуальним підходам, такою концептуальною традицією, якадосконально досліджує матеріальні фактори комунікації і втілює в собі «присутність».Міждисциплінарні методи і інтерпретаційне багатство сучасної археологічної наукифактично роблять її методологічною базою для дослідження «культур присутності».Ключові слова: присутність, матеріальні фактори комунікації, археологія,герменевтика, семіотика, знак, значення